Understanding the Dynamic Loss Modulus of NR/SBR Blends in the Glassy–Rubbery Transition Zone - Marzocca, A. J. (2025)
The motivation of this research was to analyze the dynamic properties, mainly the loss modulus, of vulcanized immiscible blends of natural rubber (NR) and styrenebutadiene rubber (SBR) in the glass transition zone, where the SBR phase is in a glassy state and the NR phase is in a rubbery state. The blends were cured at 433 and 443 K and studied around the glass transition using a dynamic mechanical analyzer. The dependence of the loss modulus on temperature was described by considering the phase separation, and the frequency dependence was also included to provide a deeper insight into the dynamic properties. This was achieved by integrating the mechanical model proposed by Zener, which considers a single relaxation time related to temperature using both the Arrhenius and Vogel–Fulcher–Tammann (VFT) relations. The best correlation with the data was obtained using the Arrhenius relationship. The activation energy of the NR phase increases with the NR content in the blend, while in the SBR phase, it varies slightly. The trends obtained are related to curative migration from the SBR to the NR phase, increasing the crosslink density at NR domain boundaries. These insights are valuable for optimizing the performance of these elastomeric blends in practical applications.